Polyhydroxyalkanoate Synthesis by Burkholderia glumae into a Sustainable Sugarcane Biorefinery Concept - de Paula, Carolina Bilia Chimello; de Paula-Elias, Fabrício Coutinho; Rodrigues, Marcela Nogueira; Coelho, Luciana Fontes; de Oliveira, Nayra Morgana Lima; de Almeida, Alex Fernando; Contiero, Jonas (Frontiers in Bioengineering and Biotechnology, 2021)
Polyhydroxyalkanoate (PHA) bioplastic was synthesized by Burkholderia glumae MA13 from carbon sources and industrial byproducts related to sugarcane biorefineries: sucrose, xylose, molasses, vinasse, bagasse hydrolysate, yeast extract, yeast autolysate and inactivated dry yeast besides different inorganic nitrogen sources. Sugarcane molasses free of pretreatment was the best carbon source, even compared to pure sucrose, with intracellular polymer accumulation values of 41.1-46.6% cell dry weight. Whereas xylose and bagasse hydrolysate were poor inducers of microbial growth and polymer synthesis, the addition of 25% (v/v) sugarcane vinasse to the culture media containing molasses was not deleterious and resulted in a statistically similar maximum polymer content of 44.8% and a maximum PHA yield of 0.18 g/g, at 34 °C and initial pH of 6.5, which is economic and ecologically interesting to save water required for the industrial processes and especially to offer a fermentative recycling for this final byproduct from bioethanol industry, as an alternative to its inappropriate disposal in water bodies and soil contamination. Ammonium sulfate was better than other tested organic nitrogen sources to trigger the PHA synthesis with polymer content ranging from 29.7 to 44.8%. GC-MS analysis showed a biopolymer constituted mainly of poly(3-hydroxybutyrate) although low fractions of 3-hydroxyvalerate monomer were achieved, which were not higher than 1.5 mol% free of copolymer precursors. B. glumae MA13 has been demonstrated to be adapted to synthesize bioplastics from different sugarcane feedstocks and corroborates to support a biorefinery concept with value-added green chemicals for the sugarcane productive chain with additional ecologic benefits into a sustainable model.